Big bad wolf kids - Zulkifli, Nur Zal Bartrisyia (Universiti Teknologi MARA, Perak, 2022)
A virtual book fair event for children via an online platform. This project is primarily concerned with digital elements such as website and mobile app. The goals of this event are to encourage children to enjoy reading books and to help them improve their daily conversation skills.